Peningkatan Hasil Belajar Tematik Terpadu dengan Menggunakan Pendekatan Saintifik di Kelas II Sekolah Dasar - Sunarti, Elly; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study is to describe the improvement of integrated thematic learning outcomes using a scientific approach in grade II of SD Istiqamah Sicincin District 2x11 Enam Lingkung Padang Pariaman Regency. This research is a class action research, consisting of 2 cycles, each consisting of planning, implementation, observation and reflection. The research subjects were teachers and 22 students at the Istiqamah Sicincin Elementary School, 2x11 Enam Lingkung District, Padang Pariaman Regency. Data from the study were obtained from the assessment of lesson plans, the implementation process, and learning outcomes. Data collection techniques using document analysis, observation sheets, tests and non-tests. This research instrument: RPP assessment sheet, observation sheet, evaluation questions and journals. The results showed an increase in: a) the assessment of RPP cycle I was 81.25%, cycle II 96.87%; b) observation of teacher activity in the first cycle 87.50% and second cycle 966.4%; c) observation of the activities of students in the first cycle 82.14% and the second cycle 96.42%; d) learning outcomes in the first cycle 81.07%, and the second cycle 88.19%. It can be concluded that a scientific approach can improve integrated thematic learning outcomes.